Characteristics of Raw Milk from Vending Machines in the Transylvania region, Romania - Mircea-Valentin MUNTEAN; Ovidiu RANTA; Ovidiu MARIAN; Vlad STOIAN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2023)
Milk is a source of proteins, lipids, vitamins and minerals and its quality can be assessed according to hygienic, nutritional, technological and sensory parameters. The main parameters are: somatic cells count, total number of germs, fat content, protein, lactose, nonfat dry matter, pH.  The aim of this study was to analyze and compare the characteristics of raw milk from vending machines in a period that includes the July-August summer months and comply qualitative standards: European Regulations 853/2004 and 854/2004 and National Veterinary and Food Safety Authority of Romania (A.N.S.V.S.A.) no. 111/2008 and no. 55/2010. Samples were collected simultaneously from 3 vending machines during a 2-year period, while the ambient temperature at the time of collection varied between 23…31 0C at the time of collection from vending machines. The following parameters were determined: total plate count (TPC), the somatic cell count (SCC), and the content of fat, protein, lactose, casein. All data were analyzed with R Studio soft-ware. Graphic analysis of results was performed with “vegan” package, based on both influence of year and automatic vending machine and related to NTG values.